CONCEPTUAL METAPHOR AND CULTURAL MODELS IN ENGLISH AND UZBEK PHRASEOLOGY: A COGNITIVE-LINGUISTIC PERSPECTIVE - Khamidova Sugdiyona,; Akhmedov Oybek Saporbayevich, (TADQIQOTLAR, 2025)
Abstract. Phraseological units (PUs)—idioms, proverbs, collocations, and set expressions—constitute a vital layer of the lexicon, encapsulating collective cognitive and cultural experience. This article examines phraseological systems in English and Uzbek through the lens of conceptual metaphor theory (Lakoff & Johnson, 1980) and cultural  models  (Kövecses,  2005).  While  earlier  studies  tended  to  treat  idioms  as arbitrary,  the  cognitive  paradigm  highlights  their  conceptual  motivation  and embodiment. Based on a comparative corpus of English and  Uzbek idioms, theyare  categorized  into  embodied,  environmental,  and  socio-cultural  domains.  Analysis reveals both universal metaphors and culture-specific models.